2020
DOI: 10.1186/s12917-020-2231-z
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of cortisol on pro-inflammatory gene expressions in LPS-, heat-killed E.coli-, or live E.coli-stimulated bovine endometrial epithelial cells

Abstract: Background: Bacterial infections are common in postpartum dairy cows. Cortisol level has been observed to increase in dairy cows during peripartum period, and is associated with the endometrial innate immunity against pathogens like E.coli. However, the mechanism underlying how cortisol regulates E.coli-induced inflammatory response in bovine endometrial epithelial cells (BEEC) remains elusive. Results: Cortisol decreased the expressions of IL1β, IL6, TNF-α, IL8, and TLR4 mRNA in BEEC treated with LPS or heat-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…Dong et al [42] demonstrated that high cortisol concentrations attenuate LPS-induced inflammatory responses in the RAW264.7 macrophage cell line by regulating the nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinases (MAPK) signaling pathways. Cui et al [54] demonstrated a two-side effect of cortisol in bovine endometrial epithelial cells (BEECs) stimulated with LPS, heat-killed Escherichia coli or live E. coli. They found that cortisol had anti-inflammatory effects on LPS-or heat-killed E. coli-stimulated BEEC, but displayed pro-inflammatory action on live E. coli-induced BEEC.…”
Section: Role Of Hpa Axis In Innate Immunitymentioning
confidence: 99%
“…Dong et al [42] demonstrated that high cortisol concentrations attenuate LPS-induced inflammatory responses in the RAW264.7 macrophage cell line by regulating the nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinases (MAPK) signaling pathways. Cui et al [54] demonstrated a two-side effect of cortisol in bovine endometrial epithelial cells (BEECs) stimulated with LPS, heat-killed Escherichia coli or live E. coli. They found that cortisol had anti-inflammatory effects on LPS-or heat-killed E. coli-stimulated BEEC, but displayed pro-inflammatory action on live E. coli-induced BEEC.…”
Section: Role Of Hpa Axis In Innate Immunitymentioning
confidence: 99%
“…This glucocorticoid regulates inflammation and immune function and its anti-inflammatory effects occur from the downregulation of several pro-inflammatory transcription factors, which then suppress synthesis of inflammatory mediators such as cytokines and prostaglandins. [43][44][45] Cortisol is produced by the adrenal glands and is controlled by adrenocorticotropic hormone (ACTH), a hormone made by the adrenal gland, and corticosteroids are known to decrease secretion of ACTH through the suppression of the hypothalamic-pituitary-adrenal axis. 46 In this study, when comparing the corticosteroid-only treatments to each other, triamcinolone suppressed cortisol levels for a significantly longer period of time compared with betamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is particular important to identify the underlying mechanism of S. aureus mastitis. A number of studies have performed to explore the host/pathogen interactions in the mammary gland by using animal model [25,26]. However, the experimental infections are costly furthermore the interactions between host defense and bacterial virulence factors are complex which make it di cult to analysis.…”
Section: Discussionmentioning
confidence: 99%